AN OVERVIEW OF DRAINAGE AND SALINIZATION PROBLEMS OF IRRIGATED LANDS†. (24th May 2019) - Singh, Ajay
Abstract: The development of irrigated agriculture is essential to feed the growing world population. Nevertheless, without proper drainage provisions, this development can result in salinization and rising groundwater table problems in irrigated areas. An effective drainage system not only improves existing agricultural lands but also brings new areas under cultivation. Poor drainage and the associated salinization cause a reduction in crop growth and yield and this reduction will be much higher if both salinization and submergence occur simultaneously. Drainage is necessary for humid as well as dry regions and it is one of the main inputs to obtain better yields per unit of agricultural area. The provision of drainage has many direct and indirect effects. This paper provides an overview of the drainage and salinization problems of irrigated lands and their impact on overall agricultural productivity. The significance of the study along with its goals and the historical development of agricultural drainage is provided. The processes involved in drainage‐associated salinization of irrigated lands and the effects of salinization and shallow groundwater tables on plant growth and yield and the environmental perspective of the problems are also detailed in the paper. Conclusions are provided that can be of use to the reader. © 2019 John Wiley & Sons, Ltd. Résumé: Le développement de l'agriculture irriguée est essentiel pour nourrir la population mondiale croissante. Néanmoins, en l'absence de dispositions de drainage appropriées, cette évolution peut entraîner une salinisation et une augmentation des problèmes de nappe phréatique dans les zones irriguées. Un système de drainage efficace améliore non seulement les terres agricoles existantes, mais permet également de cultiver de nouvelles zones. Un mauvais drainage et la salinisation associée entraînent une réduction de la croissance et du rendement des cultures. Cette réduction sera beaucoup plus importante si la salinisation et la submersion se produisent simultanément. Le drainage est nécessaire aussi bien dans les régions humides que sèches et constitue l'un des principaux intrants permettant d'obtenir de meilleurs rendements par unité de surface agricole. La fourniture de drainage a de nombreux effets directs et indirects. Ce papier fournit une vue d'ensemble des problèmes de drainage et de salinisation des terres irriguées et de leur impact sur la productivité agricole globale. L'importance de l'étude ainsi que ses objectifs et l'évolution historique du drainage agricole sont fournis. Les processus impliqués dans la salinisation des terres irriguées associée au drainage et les effets de la salinisation et de la nappe phréatique peu profonde sur la croissance de la plante et le rendement ainsi que la perspective environnementale des problèmes sont également détaillés dans le document. Des conclusions sont fournies qui peuvent être utiles aux lecteurs. © 2019 John Wiley & Sons, Ltd.